2002
DOI: 10.1007/s00441-002-0570-7
|View full text |Cite
|
Sign up to set email alerts
|

Clock mechanisms in zebrafish

Abstract: Recent research on the circadian system of the zebrafish is reviewed. This teleost has become an attractive model system because of its advantages for genetic analyses. Circadian rhythms of zebrafish behavior, visual system function, and pineal melatonin synthesis have been described, and behavioral and pineal rhythms are being used to identify and characterize clock mutants. Zebrafish heart, kidney, and embryonic cell lines contain circadian oscillators and phototransduction mechanisms for entrainment, sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
165
2
12

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 256 publications
(190 citation statements)
references
References 51 publications
(63 reference statements)
11
165
2
12
Order By: Relevance
“…Moreover, cell-autonomous circadian oscillators are present throughout the peripheral tissues and organs of zebrafish. 53,54) Importantly, zebrafish peripheral clocks are directly light-responsive. 55) Thus, in zebrafish organs and tissues, an acute light pulse can be used to transactivate clock genes and thus entrain oscillations of clock gene expression to a new light-dark cycle.…”
Section: Zebrafish As a Model System For Circadian Clock Studymentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, cell-autonomous circadian oscillators are present throughout the peripheral tissues and organs of zebrafish. 53,54) Importantly, zebrafish peripheral clocks are directly light-responsive. 55) Thus, in zebrafish organs and tissues, an acute light pulse can be used to transactivate clock genes and thus entrain oscillations of clock gene expression to a new light-dark cycle.…”
Section: Zebrafish As a Model System For Circadian Clock Studymentioning
confidence: 99%
“…53) Seven zebrafish Cry genes (zCry1a, 1b, 2a, 2b, 3, 4 and Dash) have been cloned. 53,61) Investigation of the in vitro functions of these genes has shown that they fall into two groups: one group inhibits CLOCK:BMAL-mediated transcription (repressor type CRYs: zCRY1a, 1b, 2a and 2b), whereas the other group does not inhibit transcription (non-repressor type CRYs: zCRY3, 4 and Dash).…”
Section: Redox Signaling Is Involved In the Light Entrainment Of The mentioning
confidence: 99%
See 1 more Smart Citation
“…These properties have established the zebrafish as an excellent model system that is relevant to studies of human diseases (Grunwald and Eisen, 2002). Zebrafish have also become the focus of neurobehavioral studies since larvae display learning, memory, sleep, drug addiction, and behavior phenotypes that are quantifiable and related to those seen in man (Zhdanova et al, 2001;Cahill, 2002;Guo, 2004;Orger et al, 2004;Ninkovic et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Além disso, homólogos ao gene period têm sido descritos em outros grupos, incluindo outros insetos (Barr et al 2005;Mazzotta et al 2005;Mazzoni et al 2006;Regier et al 2008), plantas (McClung, 2006) e vertebrados (Cahill, 2002;Reppert & Weaver, 2002). Nesses táxons, o gene period também foi utilizado como marcador para inferências de hipóteses filogenéticas (Barr et al 2005;Regier et al 2008) e divergência populacional (Bauzer et al 2002).…”
Section: Periodunclassified